The Unhappy Mental Health Triad: Comorbid Severe Mental Illnesses, Personality Disorders, and Substance Use Disorders in Prison Populations - Mundt, Adrian P.; Baranyi, Gergő (Frontiers in Psychiatry, 2020)
Background Information on the comorbidity of mental health problems in prison populations is scarce. The aim of the present study was to assess the prevalence of comorbidities at intake to prison between three diagnostic groups: severe mental illnesses (SMIs), personality disorders (PDs), and substance use disorders (SUDs). The co-occurrence of those disorders in prison populations may require the integration of differential treatment approaches and novel treatment trials. Methods A consecutive sample of N = 427 (229 male and 198 female) individuals committed to imprisonment in Santiago de Chile was assessed with the Mini Neuropsychiatric Interview and the Structured Clinical Interview for DSM-IV (module for borderline personality disorders) on arrival at prison. Diagnoses were a priori grouped as SMI including psychosis, bipolar disorder and major depression, PD including borderline and antisocial PD and SUD including alcohol and drug abuse or dependence. Sex stratified multivariate binary logistic regression analyses were conducted to assess sociodemographic, criminal and treatment characteristics of individuals with at least one diagnosis from each of the three diagnostic groups. Results The triad of SMI, PD, and SUD was present in n = 138 (32.3%; 95% IC: 28.0–36.9) study participants, n = 105 (45.9%; 95% CI: 39.4–52.4) of the men and n = 33 (16.7%; 95% CI: 12.1–22.6) of the women. Among those with the disorder triad, n = 129 (30.2%; 95% CI: 26.0–34.8) had major depression, PD and SUD; n = 54 (12.6%; 95% CI: 9.8–16.2) had psychosis, PD and SUD. The disorder triad was more common in men (OR = 4.86; 95% IC: 2.63–8.95), younger age (OR = 0.94; 95% CI: 0.91–0.97), and participants with lower educational levels (OR = 1.69; 95% CI: 1.01–2.82). The disorder triad was significantly associated with previous incarcerations (OR 2.60; 95% CI: 1.55–4.34) and histories of psychiatric hospitalizations (OR 2.82; 95% CI: 1.27–6.28). Discussion The complex triad of disorders from different diagnostic groups is common in prison populations, especially among young men. Successful treatment interventions may have the potential to break a cycle of repeat institutionalization in prisons and psychiatric institutions.